Teknologi Sebagai Syi’ar Agama Islam dan Peranannya dalam membentuk Karakter Akhlakul Karimah - Hisny Fajrussalam; Fany Widia Guna; Ratu Dinda Rahmah; Tasya Dila Fatimah (Yayasan Daarul Huda Kruengmane, 2023)
Today Syi'ar Islam has spread a lot in various worlds and cultures, so there are many ways to broadcast Islam. The influence of the world that is growing is an easy way to spread Islam, one of which is through technological developments. Technology can be used as a medium for Islamic syi'ar which certainly has a great opportunity for us to continue to study and spread the shi'ar of the past religion anywhere and at any time. This can affect the education of moral character in shaping human beings to be wise in using technology in addition to creating quality human beings. This research method uses a type of qualitative research with a literature study method. This research was conducted to determine the benefits of technology as Islamic syi'ar and its role in shaping the character of akhlakul karimah with sources or references that have been collected .